Tax Avoidance, Financial Performance and Growth on Firm Value : Capital Structure as Moderation - Wibowo, Jevennie; Trisnawati, Estralita (SENTRALISASI, 2025)
This research aims to determine the impact of tax avoidance, financial performance, and growth on firm value with capital structure as a moderator. It is very important for companies to study ways to increase the value of the company in order to attract investor interest in investing capital and to enhance investor confidence. The high interest of investors of all ages in investing in the company's shares can be reflected in the company's good value. Financial ratios provide an overview of a company's condition and health, especially to external parties, one of which is investors. The population of this study consists of companies listed on the IDX in the cyclical and non-cyclical consumption sectors during the period from 2020 to 2023. There are 128 test samples using the purposive sampling method. The results of this study indicate that tax avoidance does not have an impact on the value of the company, which is considered to reflect the emergence of non-compliance by the company in fulfilling its obligations as a taxpayer. Meanwhile, financial performance and growth have an impact on the value of the company, as ROA and SIZE can reflect the movement of the firm value. The role of capital structure cannot moderate the influence of tax avoidance on firm value, whereas capital structure can moderate the influence of financial performance and growth on firm value. The results of this study concludes that investors and decision-makers needs to pay attention in financial ratio when evaluating a company.